Encyclopedia of Life Sciences 2011
DOI: 10.1002/9780470015902.a0023176
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Recognition Protein Modules: The PHD Finger

Abstract: The structure of chromatin controls the accessibility to deoxyribonucleic acid (DNA) information. Posttranslational modifications (PTMs) of histones modify the architecture of chromatin and provide docking platforms for proteins that control many DNA‐templated processes. The plant homeodomain (PHD) fingers are small protein domains found in nuclear factors that interact with chromatin. Recent studies have characterised two classes among the PHD fingers, which specifically bind to ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…In the past years, the PHD finger has emerged as a versatile protein module for the recognition of the histone H3 tail [27] . In this work we show that the PHD finger of human UHRF1 represents a new mode of histone H3 recognition that requires the appendage of an additional zinc finger, relies mainly on the recognition of H3R2, and shows preference for unmethylated H3K4, although it can accommodate H3K4me3 without compromising the complex formation.…”
Section: Resultsmentioning
confidence: 99%
“…In the past years, the PHD finger has emerged as a versatile protein module for the recognition of the histone H3 tail [27] . In this work we show that the PHD finger of human UHRF1 represents a new mode of histone H3 recognition that requires the appendage of an additional zinc finger, relies mainly on the recognition of H3R2, and shows preference for unmethylated H3K4, although it can accommodate H3K4me3 without compromising the complex formation.…”
Section: Resultsmentioning
confidence: 99%
“…The cross-class targeting by a single therapeutic is also expected, because receptors and enzymes for the same substrate may differ by backbone topology, yet contain similar binding sites 34 . In addition, some protein targets contain multiple small-molecule binding sites, which may allow chemically diverse drugs to bind [35][36][37] . For example, it has been shown that protein kinase inhibitors such as, imatinib and nilotinib, are also able to target smoothened receptor of the Hedgehog pathway; celecoxib targets prostaglandin G/H synthase 2, carbonic anhydrases, and several nuclear receptors 38,39 .…”
Section: Discussionmentioning
confidence: 99%